2016
DOI: 10.1016/bs.mie.2015.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium Labeling Together with Contrast Variation Small-Angle Neutron Scattering Suggests How Skp Captures and Releases Unfolded Outer Membrane Proteins

Abstract: In gram-negative bacteria, the chaperone protein Skp forms specific and stable complexes with membrane proteins while they are transported across the periplasm to the outer membrane. The jellyfish-like architecture of Skp is similar to the eukaryotic and archeal prefoldins and the mitochondrial Tim chaperones, that is α-helical ‘tentacles’ extend from a β-strand ‘body’ to create an internal cavity. Contrast variation small-angle neutron scattering (SANS) experiments on Skp alone in solution and bound in two di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 75 publications
5
41
1
Order By: Relevance
“…uOMPs are expected to exist in a relatively collapsed, molten globule state in the absence of chaperones (50). This collapsed conformation is maintained when uOmpA171 is bound by the other major chaperone in the uOMP biogenesis pathway, Skp (60,61). To determine whether the overall size and shape of a uOMP changes when bound to SurA, we measured the hydrodynamic properties using small angle neutron scattering (SANS).…”
Section: Resultsmentioning
confidence: 99%
“…uOMPs are expected to exist in a relatively collapsed, molten globule state in the absence of chaperones (50). This collapsed conformation is maintained when uOmpA171 is bound by the other major chaperone in the uOMP biogenesis pathway, Skp (60,61). To determine whether the overall size and shape of a uOMP changes when bound to SurA, we measured the hydrodynamic properties using small angle neutron scattering (SANS).…”
Section: Resultsmentioning
confidence: 99%
“…Examples of this methodology in biological systems are presented in the literature [25], [47], [48], [49], [50], [51]. The basic idea of this method is that the scattered intensity depends on Δρ (see Eq.…”
Section: Overview Of Small-angle Neutron Scatteringmentioning
confidence: 99%
“…These techniques are useful for gaining information on the structural arrangement and dynamics of proteins as well as establishing correlations with stability in amorphous phases. Readers interested in other neutron techniques, or other applications of neutron scattering in biology, are referred to general reviews discussing the fundamentals of neutron scattering [15], [16], [17], [18], [19], neutron scattering for structural biology studies [13], [14], [20], [21], and contrast matching techniques for biological samples [22], [23], [24], [25].…”
Section: Introductionmentioning
confidence: 99%
“…Small-angle Neutron Scattering (SANS , See Glossary) experiments have demonstrated that the α-helical arms of Skp are flexible to accommodate the unstructured uOMP [19]. Structural modeling of uOMP bound to Skp revealed that the uOMP is not entirely encapsulated but protrudes from the Skp cavity (Figure 3).…”
Section: How Do Periplasmic Chaperones Safeguard Uomps Without An Extmentioning
confidence: 99%